Pour un accueil en santé des personnes immigrantes francophones au Nunavut - état de situation - Réseau Santé en français au Nunavut (2021)

Trousse d’accompagnement pour l’examen médical du nouvel arrivant - Sanou, Baroma; Gauthier, Alain; Chomienne, Marie-Hélène; Prud'homme, D.; Kpazaï, G. (2018)
fs-ref-orig: Sanou, B., Gauthier, A., Chomienne, M.-H., Prud'homme, D. et Kpazaï, G. (2018). Trousse d’accompagnement pour l’examen médical du nouvel arrivant. Centre de recherche en santé dans les milieux ruraux et du nord, Institut du Savoir Montfort et Centre de la santé communautaire du Grand Sudbury. fs-code-orig: Sanou-2018

Processus de développement d’une trousse d’accompagnement pour l’examen médical des nouveaux arrivants francophones : un exemple de coopération - Sanou, Boroma; Beaudoin, Monique; Gauthier, Alain P.; Chomienne, Marie-Hélène; Prud’homme, Denis; Kpazaï, Georges (Revue de la Diversité de la Recherche en Santé, 2020)
While over the half of Francophone immigrants living in Ontario come from Africa and the Caribbean, Canadian-trained health professionals are not sufficiently familiar with the health problems that newcomers may face. With this in mind, in a multi-disciplinary partnership, the Center for Rural and Northern Health Research, the Centre de santé communautaire du grand Sudbury, l’Institut du savoir Montfort, the School of Human Kinetics at Laurentian University, and a group of French-speaking immigrants from the City of Greater Sudbury, developed using a collaborative research approach, a newcomer’s medical examination toolkit for health professionals and social services. The toolkit development process involved several steps: 1) establishing a partnership between the above-mentioned organizations; 2) literature review to identify the most common health problems; 3) selection of the most common problems that are not necessarily those that health professionals encounter in everyday practice; 4) writing of draft versions with emphasis on some important aspects of the disease; 5) validation of the fact sheets by the partners; 6) the restitution of the final fact sheets (25 fact sheets including 3 on the general examination, 10 related to certain tropical diseases, 8 sheets related to the signs and symptoms most frequently encountered by health professionals and the other 4 on health care in Ontario); and 7) the development of a digital infograph to ensure greater visibility of the Toolkit for the medical examination of Francophone newcomers.

Guide de navigation du réseau de la santé et des services sociaux du Manitoba - Santé en français (2024)